Folklore students at a party at Émile Benoit’s house - Ledrew, Minette (1990)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « Report on a Folklore Fieldtrip at Mainland (La Grand'Terre) Port-au-Port Peninsula, Newfoundland March 10-14, 1990 ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "Report on a Folklore Fieldtrip at Mainland (La Grand'Terre) Port-au-Port Peninsula, Newfoundland March 10-14, 1990".